Pembinaan Baca Tulis Qur’an Menggunakan Metode Gerak Tangan di TPQ Al Ikhlas Kabupaten Padang Pariaman - Syah, Muhammad Aldian; Kustati, Martin; Amelia, Rezki; Gusmirawati, Gusmirawati (Al-DYAS, 2024)
This training aims to evaluate the effectiveness of the Hand Movement method in teaching reading and writing of the Qur'an (BTQ) at the Al Ikhlas Qur'an Education Park (TPQ) in Padang Pariaman. The Hand Movement method, which integrates Hand Movement with the teaching of letters and tajwid, is expected to enhance the reading and writing skills of children in the TPQ. This training employs the Participatory Action Research (PAR) method, a process aimed at scientifically studying issues to guide, improve, and evaluate. The PAR method is useful for addressing problems and fulfilling the practical needs of the community, as well as for the production of knowledge and social-religious change (Afandi, 2022). Data were collected through tests of reading and writing ability of the Qur'an and observations of the method's implementation. The results of the assistance indicate that the use of the Hand Movement method significantly improves the reading and writing skills of the students. Additionally, this method has also proven to enhance student motivation and engagement in the learning process. These findings contribute positively to the development of BTQ teaching methods at TPQ and can be applied in similar educational institutions to improve the effectiveness of Qur'an teaching.